BIOAKUMULASI RESIDU CEMARAN DDT DAN KLOROTALONIL PADA IKAN KARPER DAN NILA DANAU BUYAN BULELENG BALI - Manuaba, Ida Bagus Putra (Bumi Lestari; Vol 9 No 2 (2009), 2009)
Analysis of DDT and chlorotalonil bioaccumulation on carp and nile fish tissues at Buyan Lake were performed. The study involve two step activities, i.e. field study for gaining sampling zone and sample needed, followed by laboratory works for obtaining DDT and chlorotalonil residual bioaccumulation on fish. Sample preparation for this purposed was carried out following a standard method. Gas chromatography was employed for determining accumulation of DDT and chlorotalonil. Average bioaccumulation of DDT on carp and nile is 16.6 and 9.6 ppb, respectively, while, average chlorothalonil bioaccumulation on the same fishes is 11.9 and 13.3 ppb, respectively.
Keywords: DDT, chlorotalonil, bioaccumulation, a standar method